A Flexible Online Apparatus for Projectile Launch Experiments - Paiva, Carlos (2017)
In order to provide a more flexible learning environment in physics, the developed projectile launch apparatus enables students to determine the acceleration of gravity and the dependence of a set of parameters in the projectile movement. This apparatus is remotely operated and accessed via web, by first scheduling an access time slot. This machine has a number of configuration parameters that support different learning scenarios with different complexities.